Case report Cold urticaria: a case report - Gomułka, Krzysztof (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
In the group of skin lesions of the type represented by chronic urticaria, a significant proportion comprises physical urticaria, which may involve even about 15% of patients. Typical skin lesions appear by the tripping of a variety of physical stimuli, so the most recognizable physical urticaria belongs to different groups, such as urticaria from oppression, from the cold and cholinergic urticaria. The underlying mechanisms causing physical urticaria are poorly understood; mainly non-immunological mechanisms have been implicated. Acquired cold urticaria is caused by cooling of the skin or mucous membranes and is considered as the only physical urticaria occurring in children. In the case of strong, sudden cooling (e.g. after consumption of ice cream, cold drinks or contact with cold water) in susceptible individuals skin lesions occur and this may even lead to the anaphylactic shock. Diagnosis of cold-induced urticaria is based on clinical presentation and a helpful exposure test, which involves application of an ice-cube on the surface of the patient's forearm. Treatment consists of supportive systemic corticosteroids, antihistamines and antileukotrienes. It is regarded that first of all prevention is necessary, which consists of proper information for patients, limitation of situations connected with sudden cooling of the body and eating cold food and drinks. Below, we describe a case of a 32-year-old female admitted to the Department of Internal Medicine, Geriatrics and Allergology, Medical University in Wroclaw to undergo diagnostic tests of chronic urticaria. According to information obtained from the clinical presentation and after the allergological diagnostic procedures, acquired cold urticaria was diagnosed.